KEPADATAN FITOPLANKTON DI PESISIR PERAIRAN KABUPATEN LAMONGAN, JAWA TIMUR - Zaenal Arifin; Apri Arisandi (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTThe coastal area of Lamongan Regency is an area that has a high population density so that it is possible for many organic and non-organic materials to enter the waters. Phytoplankton are aquatic organisms that can be used as indicators of water quality parameters because they are primary producer in the waters. This study is to determine the density of phytoplankton with diversity index, uniformity index and dominance index. This research was conducted from December 2018 to January 2019. Then identification of phytoplankton and analysis of the laboratory of marine science at University of Trunojoyo Madura. Sampling is done at two different stations. Analysis of phytoplankton density using haemocytometer and T test for analysis of phytoplankton density statistics. Phytoplankton found consisted of 3 classes (Bacillarophyceae, Cyanophyceae and Dinophyceae) with 22 genus. Total density of phytoplankton 2,896 cells / l, where station 1 (point A 4,125 cells / l, point B 2,750 cells / l) and station 2 (point C 3,125 cells / l, point D 2,500 cells / l, point E 2,625 cells / l and point F 2,250 cells / l) fall into the mesotrophic category. The diversity index is 1,864-2,494, the uniformity index is 0,750-0,945 and the dominance index is 0,0917–0,27551, where phytoplankton is still stable between the two stations. With the value of environmental parameters temperature 28.9 - 31.3 ˚C, Dissolved Oxygen 5.6-6.2 mg / ml, Salinity 27.6-30.3 ppt, pH 6.97-7.32 and brightness 26, 6-100 cm.Keywords: Lamongan, Phytoplankton and DensityABSTRAKDaerah pesisir Kabupaten Lamongan merupakan daerah yang mempunyai kepadatan penduduk yang cukup tinggi sehingga dimungkinkan banyak bahan-bahan organik dan non organik yang masuk kedalam perairan. Fitoplankton merupakan organisme perairan yang mampu dijadikan sebagai indikator parameter kualitas perairan karna bersifat produsen primer di perairan. Penelitian ini untuk mengetahui kepadatan fitoplankton dengan indeks keanekaragaman, indeks keseragaman dan indeks dominasi. Penelitian ini dilakukan dari bulan desember 2018 sampai januari 2019. Kemudian dilakukan identifikasi fitoplankton dan analisis dilaboratorium ilmu kelautan Universitas Trunojoyo Madura. Pengambilan sampel dilakukan di dua stasiun yang berbeda. Analisis kelimpahan fitoplankton menggunakan haemocytometer dan uji T untuk analisa statistik kepadatan fitoplankton. Fitoplankton yang ditemukan terdiri dari 3 kelas (Bacillarophyceae, Cyanophyceae dan Dinophyceae) dengan 22 genus. Total kepadatan fitoplankton 2.896 sel/l, dimana stasiun 1 (titik A 4.125 sel/l, titik B 2.750 sel/l) dan stasiun 2 (titik C 3.125 sel/l, titik D 2.500 sel/l, titik E 2.625 sel/l dan titik F 2.250 sel/l) masuk dalam kategori mesotrofik. Indeks keanekaragaman sebesar 1,864-2,494, indeks keseragaman sebesar 0,750-0,945 dan indeks dominasi sebesar 0,0917–0,27551, dimana fitoplankton masih setabil antara kedua stasiun. Dengan nilai parameter lingkungan suhu 28,9 – 31,3 ˚C, Oksigen Terlarut 5,6-6,2 mg/ml, Salinitas 27,6-30,3 ppt, pH 6,97-7,32 dan kecerahan 26,6-100 cm.Kata kunci: Lamongan, Fitoplankton dan Kepadatan